THE CORRELATION BETWEEN BODY COMPOSITION AND AEROBIC ENDURANCE AS A PREDICTOR OF SPORTS PERFORMANCE IN 16–18-YEAR-OLD SWIMMERS (Rehabilitation and Recreation, 2024)
In the presented article, the components of body composition and working capacity factors were analyzed. The obtained data were correlated with the volume of training and athletic performance. The research was conducted on eight swimmers from the MUKS Astoria club in Bydgoszcz. In relation to the discussed issues, four hypotheses were put forward. The first two suggest that due to the applied training volume, differences in the components of body composition and aerobic capacity will be noticeable. The next hypothesis concerns the influence of the components of body composition on performance. The fourth includes the statement that the applied training volume, performance, and the components of body composition will affect the athletic outcome. The research showed minor changes in the components of body composition due to the training volume used. The performance was improved, both of the oxygen threshold, power, and AT threshold. Performance did not correlate with the training volume. It is possible to assume that the decisive factor in improving performance is the qualitative component of training loads, i.e., intensity. A statistically significant correlation between performance and the components of body composition was noted. Swimmers with less fat (FAT) and more water and muscle mass (SMM) had better performance. In the group under research, the FAT and SMM values were in line with the reference values. Correlating performance and the components of body composition with athletic results, depending on the distance and swimming style, a statistically significant correlation was observed. In the backstroke style, it was shown that Vo2 max and power do not play such a crucial role since it is a technical style. Moreover, backstroke athletes characterized by lower SMM, water content and higher FAT achieved better sports results. In the classical style, swimmers with a higher oxygen threshold and maximum power, as well as higher water and SMM content and less FAT, achieved better athletic performance. In butterfly, great power indicated a better athletic result. Both styles require high physical fitness and significant energy expenditure. For the 100-meter distance, a higher FAT content allowed swimmers to float higher in the water and achieve a better athletic outcome. A similar correlation was found when analyzing the 50-meter distance, confirming that for sprinters, higher FAT and lower SMM contribute to improved sports performance.
Keywords: composition, performance, swimmers, correlation, distance, results